Cross-reactive antibodies binding to H4 hemagglutinin protect against a lethal H4N6 influenza virus challenge in the mouse model - Fatima Amanat; Philip Meade; Shirin Strohmeier; Florian Krammer (Emerging Microbes and Infections)
Influenza viruses of the H4 subtype are widespread in wild birds, circulate in domestic poultry, readily infect mammals, and tolerate the insertion of a polybasic cleavage site. In addition, serological evidence suggests that humans working with poultry are exposed to these viruses. While H4 viruses are not of immediate pandemic concern, there is a lack of knowledge regarding their antigenicity. In order to study viruses of the H4 subtype, we generated and characterized a panel of antibodies that bind a wide variety of H4 hemagglutinins from avian and swine isolates of both the Eurasian and North American lineage. We further characterized these antibodies using novel recombinant H4N6 viruses that were found to be lethal in DBA/2J mice. Non-neutralizing antibodies, which had activity in an antibody dependent cell-mediated cytotoxicity reporter assay in vitro, protected mice against challenge in vivo, highlighting the importance of effector functions. Our data suggest a high degree of antigenic conservation of the H4 hemagglutinin.